Effect of Low-Frequency Electrical Stimulation Combined with Abdominal Acupoint Massage on Postoperative Gastrointestinal Function Recovery after Cesarean Section: A Prospective Randomized Study - Xiaodan Zou; Meiling Cai (IMR Press, 2024)
Background: This study aimed to investigate the effects of low-frequency electrical stimulation combined with abdominal acupoint massage on the recovery of gastrointestinal function following cesarean section. Methods: A total of 60 postoperative patients were randomly assigned to either the control group (group A, n = 30) or the observation group (group B, n = 30) between January 2021 to December 2021. The control group received conventional interventions, while the observation group received a nursing intervention consisting of low-frequency electrical stimulation combined with abdominal acupoint massage starting at 10-12 hours after the operation. The primary outcomes included the time to first bowel sound, time to flatus, time to defecation, and time to lactation. The secondary outcomes included postoperative visual analogue scale (VAS) pain scores, the rate and severity of abdominal distension, and serum levels of prolactin (PRL) and vasoactive intestinal peptide (VIP). Results: The observation group had significantly earlier restoration of bowel sounds, passage of first flatus, and first defecation than the control group (p < 0.001). The VAS scores in the observation group were significantly lower than those in the control group at 24 h, 48 h, and 72 h after the operation (p < 0.001). The incidence of abdominal distension in the observation group (13.3%, 4/30) was lower than that in the control group (36.7%, 11/30) (p < 0.05). Furthermore, compared to the control group, the observation group showed a significant increase in serum PRL levels and a significant decrease in VIP levels after treatment (p < 0.001). Conclusions: The application of low-frequency electrical stimulation combined with abdominal acupoint massage after cesarean section can expedite the recovery of gastrointestinal function and reduce pain and complications, such as abdominal distension. This approach can be used in clinical practice to accelerate the recovery of intestinal function after cesarean section. Clinical Trial Registration: The study was registered with the ISRCTN registry (https://www.isrctn.com/), registration number: ISRCTN16533743.